2008
DOI: 10.5194/acp-8-7507-2008
|View full text |Cite
|
Sign up to set email alerts
|

Polar organic tracers in PM<sub>2.5</sub> aerosols from forests in eastern China

Abstract: Abstract. Photooxidation products of biogenic volatile organic compounds, mainly isoprene and monoterpenes, are significant sources of atmospheric particulate matter in forested regions. The objectives of this study were to examine time series and diel variations of polar organic tracers for the photooxidation of isoprene and α-pinene to investigate whether they are linked with meteorological parameters or trace gases, and to determine their carbon contributions. In addition, the biogenic secondary organic car… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(43 citation statements)
references
References 50 publications
(56 reference statements)
2
41
0
Order By: Relevance
“…So data for PM 2.5 concentration and composition could not be systematically acquired in most parts of China by now. In China, studies for PM 2.5 have been gradually carried out since 2000, and mainly focused on the urban areas of the Pearl River Delta (Cao et al, 2004;Hagler et al, 2006;Duan et al, 2007;, the Yangtze River Delta (Ye et al, 2003;Yang et al, 2005;Wang et al, 2008;Li et al, 2011), and the BTH region.…”
Section: P S Zhao Et Al: Concentrations and Chemical Compositions mentioning
confidence: 99%
“…So data for PM 2.5 concentration and composition could not be systematically acquired in most parts of China by now. In China, studies for PM 2.5 have been gradually carried out since 2000, and mainly focused on the urban areas of the Pearl River Delta (Cao et al, 2004;Hagler et al, 2006;Duan et al, 2007;, the Yangtze River Delta (Ye et al, 2003;Yang et al, 2005;Wang et al, 2008;Li et al, 2011), and the BTH region.…”
Section: P S Zhao Et Al: Concentrations and Chemical Compositions mentioning
confidence: 99%
“…Further, the aerosol accumulation mode number concentrations in this region are postulated to be the highest in the world (Andreae and Rosenfeld, 2008). Up until now, several studies have been conducted in urban and forest areas from North to South China, focusing on the SOA tracers from the oxidation of BVOCs such as isoprene, monoterpenes and sesquiterpenes (Hu et al, 2008;Wang et al, 2008;Fu et al, 2010;Gao et al, 2012). During the ACE-Asia campaign, remarkably high organic carbon concentrations (mean 4 µgC m −3 up to 6.5 km altitude) in the free troposphere were obtained by aircraft measurements (Huebert et al, 2003).…”
Section: P Q Fu Et Al: Aircraft Measurements Of Polar Organic Tracmentioning
confidence: 99%
“…Nevertheless, our results are similar to those (0-1380 ng m −3 , 250 ng m −3 ) reported in Research Triangle Park, NC, in 2006 (Offenberg et al, 2011), and also similar to those reported at the ground surface in China. For example, Wang et al (2008) investigated the summertime SOC levels from isoprene oxidation in four forests in East China; the estimated isoprene-SOC concentrations were 320 ng m −3 for Changbai Mountains, 30 ng m −3 for Chongming, 160 ng m −3 for Dinghu, and 270 ng m −3 for Hainan. Such a similarity strongly suggests the presence of a large amount of biogenic SOA not only near the ground surface but also aloft in the troposphere over central China.…”
Section: Vertical Distributions Of Poa and Soa Tracersmentioning
confidence: 99%
“…Atmospheric oxidation of BVOCs by the hydroxyl radical, ozone and nitrate radical leads to the formation of more oxidised compounds, which can lead to the formation of secondary organic aerosol (SOA). The majority of studies of organic aerosol composition in forested regions have taken place in boreal (Kristensen and Glasius, 2011;Kallio et al, 2006) and temperate forests (Gomez-Gonzalez et al, 2012;Surratt et al, 2007;Wang et al, 2008) of the Northern Hemisphere. The tree species found in tropical rainforests are very different, being dominated by lowland evergreen broadleaf rainforest.…”
Section: Introductionmentioning
confidence: 99%